The Influence of Social Support, Self-Esteem and Self-Efficacy on Academic Achievement - Maspupatun, Imas; Eddy Wibowo, Mungin; Sugiyo, Sugiyo (Universitas Negeri Semarang, 2021)
Academic achievement is a prominent indicator of student’s learning success. However, not all students can meet this goal. Therefore, this study analyzed the influence of social support, self-esteem, and self-efficacy on the academic achievement of MAN 5 Cirebon students. As many as 70 students from grades X and XI were selected using purposive sampling technique. Their data were collected using instruments such as the scales of social support, self-esteem, and self-efficacy. It was revealed that social support, self-esteem, and self-efficacy had a positive influence on academic achievement. These findings emphasize the importance of the development of self-esteem, self-efficacy, and the reinforcement of social support to help students improve their achievement